A Study of Thermal Properties of Some Nematogenic Schiff’s Bases - Ridha, S.H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2019)
The thermal properties of four nematogenic Schiffâ€™s bases, n-butyl-to-n-heptyl of bis (4-n-alkyloxybenzylidine)-2,3,5.6- tetramethyl-1, 4-phenylenediamine, have been studied. The transition temperatures and enthalpies of transition were examined by differential scanning calorimeter (DSC). Several correlations were carried out; those included the relations between transition temperatures, enthalpies and entropies of transition with increasing the number of carbon atoms in the terminal alkyl chains. In addition, new regular relations were found between the ratio of the enthalpies and of the entropies, for noematic-isotropic transition and crystal-isotropic transition ( Î”Î—Î-i/AHC-I, Î”SN-1/ ASC-I ), with increasing terminal alkyl chain lengths. Many interesting conclusions, concerning the relation between the anisotropic molecular shape and the thermal properties of the above nematogens, have been arrived at.